Analysis of Electric Car Growth in Support of Sustainable Energy Transition and Transportation Solutions in Indonesia - Moh Adistian; Luthviyah Ismayati; Evi Karyani; Mita Mita; Deri Apriadi; Yulianah Yulianah (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the role of electric vehicle growth in supporting sustainable energy transition efforts and transportation sustainability in Indonesia by examining energy efficiency, infrastructure readiness, and electricity system challenges. Research Method: This study employed a descriptive qualitative approach using a Systematic Literature Review (SLR). Secondary data were collected from peer-reviewed journal articles, government reports, and energy policy publications indexed in Scopus, ScienceDirect, SpringerLink, Wiley Online Library, and Google Scholar from 2020 to 2025. The analysis used thematic synthesis involving screening, categorization, and interpretative analysis. Results and Discussion: The findings indicate that electric vehicles provide higher energy efficiency, lower operational costs, and reduced dependence on fossil fuels. However, EV sustainability remains dependent on the readiness of the charging infrastructure, the electricity grid's capacity, the integration of renewable energy, and the development of battery technology. Implications: The findings emphasize the importance of integrated policies involving renewable energy expansion, charging infrastructure development, and electricity system strengthening. Originality: This study offers an integrative perspective that links EV adoption, energy transition readiness, electricity systems, and sustainability challenges in the Indonesian context.